Bioassay guided isolation of an antidermatophytic active constituents from the stembarks of entada spiralis ridl - Harun, Aiza; Mat So'ad, Siti Zaiton; Mohd Hassan, Norazian; Che Mohd Ramli, Neni Kartini (2014)
Entada spiralis ridl (lenguminoceae) is a liana or woody climber that grows in the wild in Malaysia and is known locally as "Beluru" or "Sintok". The isolation and characterization of the chemical constituent from an active fraction of E. spiralis stem bark has been carried out. Our previous study revealed that methanol extract of E. spiralis stem bark exhibited promising antifungal activity against three dermatophyte strains, namely Trichophyton mentagrophytes ATCC 9533, Trichophyton tonsurans ATCC 28942 and Microsporum Gypseum ATCC 24102 that cause skin infection. This study was performed to elucidate the structure of active constituent known as ester saponin from the active fraction of E. spiralis stem bark. The factions were prepared using fractionation process and repeated antifungel test was conducted to identify the most active fraction. The structure elucidation of this compound was based on spectroscopis data (1H, 13C NMR, HMQC, HMBC and DEPT135) and comparison with literature. on the basis of spectroscopis analysis, the compound was identified as 28-α,L-rhamnopyranosyl-18,21,22-trihydroxy-12-en-29-(2-acetylamino-β-Dglucopyranosyl)triterpene ester. The current study provides important baseline information for the use of E. spiralis for the treatment of skin infection caused by the microorganism investigated in this study.